Ambulatory Pessary Trial Unmasks Occult Stress Urinary Incontinence - Bilal Chughtai; Sara Spettel; Jonathan Kurman; Elise De (Hindawi Limited, 2012)
Objective. We evaluated the use of a one-week ambulatory pessary trial in predicting patients' postoperative outcomes for occult stress incontinence. Methods. Patients with anterior vaginal wall prolapse were offered a pessary trial to predict response to reconstruction. We performed a retrospective review of 4 years of cases. All patients underwent a detailed evaluation including videourodynamics with and without pessary reduction. Results. Twenty-six patients completed the 1-week pessary trial. Ten (38%) women showing no evidence of stress urinary incontinence (SUI) underwent surgical repair of prolapse without anti-incontinence procedure. None of these patients had SUI postoperatively. Sixteen women (61%) had occult stress urinary incontinence on evaluation and underwent concurrent sling procedure. Three (19%) of these patients were identified by the pessary trial alone. Twenty-five of the 26 patients were without clinical stress incontinence at a mean follow up of 12 months (range 4-37 months). The pessary trial correctly predicted persistent urgency in six patients and persistent frequency in five. No patients with SUI or persistent voiding difficult were missed in a pessary trial. Conclusion. An ambulatory pessary trial is an effective, easy, and inexpensive method to approximate anatomic results achieved by surgery under real-life conditions. In our series, 20% of patients with occult SUI were identified by pessary trial alone.